A rare case of Fahr's syndrome with dissociative amnesia - Faizal Muhammad; Wilson Arpin; Yeremia Suryo Pratama; Cynthia Hanny Lestari; Pepi Budianto; Rivan Danuaji; Ervina Arta Jayanti Hutabarat; Stefanus Erdana Putra; Muhammad Hafizhan (Faculty of Nursing Universitas Padjadjaran, 2022)
Background: Fahr's syndrome (FS) is a movement and psychiatric disorder characterized by symmetrical and bilateral calcification of the basal ganglia. Dissociative amnesia is a rare psychiatric disorder that occurs after stressful events and is classified as a dissociative disorder. In addition, dissociation is the process by which the mind conceals stressful events from consciousness. Several neuropsychiatric manifestations in FS have been reported. However, due to their rarity, FS and dissociative amnesia can be misdiagnosed. Case: A 43-year-old female presented with Parkinsonian symptoms and an inability to recall important personal information. FS and dissociative amnesia were diagnosed after a thorough medical, psychiatric, and diagnostic investigation. Subsequently, correction of calcium and phosphate levels by Î±-hydroxy-vitamin-73 D3 and psychotherapy were administered for two-months until there were no neuropsychiatric symptoms reported. Conclusion: This research highlights a rare case of FS with dissociative amnesia which pathophysiology is not completely understood due to limited research.